Can text messaging be used as an effective method for collecting quality and detailed evaluation data from students on clinical placements?. (2013) - Struthers, J.; Irvine, P.; Jackson, C.
Abstract : Background : Collecting timely evaluation from students on their clinical placements for quality assurance purposes is challenging. Prompt responses can help placement organisers improve the experience for the next cohort of students. Aims : This paper examines the success and limitations of using text messages to collect anonymous, instant, and detailed evaluation from students on clinical placements. Method : Second year medical students attending 9 placements were sent a series of 5 evaluation statements immediately after their placement. Results : The response rate for the first question was 55.73% ( n  = 124) falling to 46.16% for the completion of all 5 questions. The number of words used in the free text responses ranged from 1 to 95. The median value for words used per text was 10 when asked to make positive comments and 7 when asked to identify negative issues. Conclusion : Text messaging is an effective method of collecting good quality and timely evaluation from students on placements. The quality of information received provided placement organisers with sufficient information to respond to issues in a timely manner. The method is limited by the number of questions that can realistically be asked. The concerns that students would be unwilling to engage with this method seems unfounded.